Analisis Kinerja Keuangan terhadap Pertumbuhan Laba Industri Barang Konsumsi Syariah - Aqnes Devita Efendy; Maheni Ika Sari; Rusdiyanto Rusdiyanto (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to analyze the effect of financial performance on profit growth in the Islamic consumer goods industry. The data used is secondary data in the form of financial reports that have been published through the official website www.idx.co.id. The selection of this research sample used a purposive sampling method and obtained as many as 20 companies that met the criteria. Methods of data analysis using multiple linear regression with SPSS version 25.0. Based on the research results, it is known that CR has a good average value according to industry standards, namely 200%, DAR has a fairly good average value according to industry standards, namely 35%, TATO has a fairly good average value according to industry standards. industry, namely 2 times, NPM has a fairly good average value in accordance with industry standards, namely 20%. The conclusions from this study are that partially the current ratio, debt to asset ratio, total asset turnover, net profit margin have a positive and significant effect on profit growth in the Islamic consumer goods industry. Keywords: CR, DAR, NPM, Profit Growth, TATO